2010
DOI: 10.1001/archinternmed.2009.471
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Diabetic Nephropathy by Tight Target Control in an Asian Population With Type 2 Diabetes Mellitus

Abstract: Diabetic nephropathy can be delayed by tight simultaneous achievement of multiple ADA-recommended targets. This multifactorial intervention should be started in patients with diabetes and normoalbuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 24 publications
4
33
1
Order By: Relevance
“…Although longer T2DM duration was seen in the DN patients versus normoalbuminuric patients (with macroalbuminuric patients having lower disease duration than microalbuminuric patients), it did not attained statistical significance (p = 0.052), conflicting with previous findings [57][58][59] that longer T2DM duration increases the risk of DN development. However, in our study univariate analysis revealed that in addition to ACE genotype, significantly higher HbA1c [59][60][61], and creatinine levels [58,59,61] were associated with renal injury, in accord with other studies on DN development.…”
Section: Discussionsupporting
confidence: 91%
“…Although longer T2DM duration was seen in the DN patients versus normoalbuminuric patients (with macroalbuminuric patients having lower disease duration than microalbuminuric patients), it did not attained statistical significance (p = 0.052), conflicting with previous findings [57][58][59] that longer T2DM duration increases the risk of DN development. However, in our study univariate analysis revealed that in addition to ACE genotype, significantly higher HbA1c [59][60][61], and creatinine levels [58,59,61] were associated with renal injury, in accord with other studies on DN development.…”
Section: Discussionsupporting
confidence: 91%
“…13,14 Therefore, early intensive glycemic and blood pressure control can effectively prevent the occurrence of diabetic nephropathy. 15 The presence of peripheral neuropathy, PVD, and poor glycemic control in conjunction with minor foot trauma increases the likelihood that patients with diabetes will develop foot ulcers. 16 Ulcers, in turn, often progress to infections of the surrounding tissues, osteomyelitis, gangrene, and amputation.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the multicausality of chronic kidney disease, attainment of multiple treatment goals in blood pressure, glucose and lipid control and blockade of the RAAS was associated with increased probability of remission, and reduced probability of progression of diabetic albuminuria [40,41]. In a multicentre randomized study involving 205 Chinese type 2 diabetic patients with renal insufficiency, patients treated with structured care delivered by a doctornurse team were 3-fold more likely to attain multiple treatment goals compared to usual care (61 vs. 28%).…”
Section: Multifactorial Treatment To Prevent Diabetic Nephropathymentioning
confidence: 99%